Billy's bootcamp. AB bootcamp [videorecording (DVD)]. - Blanks, Billy (GoodTimes Entertainment, 2004)
"With AB bootcamp, Billy introduces a whole new approach to attack the fat, and give you the slimmed-down midsection you've always dreamed of"--Container.